ANALYSIS OF CAREER MATURITY ON FINAL YEAR STUDENTS - Fadlila, Inka; Sumastuti, Efriyani; Sijabat, Rauly (Stability: Journal of Management and Business, 2023)
Career maturity is an individual's readiness to make career decisions supported by strong information about work, based on the exploration that has been done. The problem behind this research is the low level of maturity of final year students in Semarang City. This can be seen from BPS (2022) which shows the unemployment rate fluctuates. This research uses quantitative methods. The data collection process was carried out by distributing questionnaires through google form to all Semarang City final year students who were completing their thesis, with a sample of 125 students as respondents. The data analysis technique that will be used is by using SPSS 26 for windows software. The results of this study indicate that self efficacy and internal locus of control have a significant effect on career maturity because they have a sig value. 0,05. While self-concept, family support, and emotional intelligence have no significant effect on career maturity because the sig value 0.05. The coefficient of determination (R2) has an adjusted R square value of 0.662, which shows that the variables of self efficacy, internal locus of control, self-concept, family social support, emotional intelligence are 6.62% of career maturity.